2014
DOI: 10.1002/etc.2673
|View full text |Cite
|
Sign up to set email alerts
|

Selenium bioaccumulation in fish exposed to coal ash at the Tennessee Valley Authority Kingston spill site

Abstract: In December 2008, 4.1 million cubic meters of coal ash were released into the Emory and Clinch Rivers by the Tennessee Valley Authority Kingston Fossil Plant. Coal ash contains several contaminants, including the bioaccumulative metalloid selenium (Se). Because Se is predominantly accumulated in aquatic organisms through dietary rather than aqueous exposure, tissue-based toxicity thresholds for Se are currently being considered. The proposed threshold concentrations range between 4 μg/g and 9 μg/g Se (dry wt.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The concentrations of Se in the fish collected for this investigation were similar to concentrations previously reported for redear sunfish whole bodies and muscle tissue at these and other nearby coal ashexposed sites in related bio-assessment efforts associated with the Kingston ash spill (Adams et al, 2012a;Mathews et al, 2014). Both whole body and especially ovary concentrations of Se at these locations have remained below proposed freshwater ambient water quality chronic criteria for aquatic life of 15.2 mg/kg (d.w.) in fish ovary/eggs and 8.1 mg/kg for fish whole bodies (USEPA, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The concentrations of Se in the fish collected for this investigation were similar to concentrations previously reported for redear sunfish whole bodies and muscle tissue at these and other nearby coal ashexposed sites in related bio-assessment efforts associated with the Kingston ash spill (Adams et al, 2012a;Mathews et al, 2014). Both whole body and especially ovary concentrations of Se at these locations have remained below proposed freshwater ambient water quality chronic criteria for aquatic life of 15.2 mg/kg (d.w.) in fish ovary/eggs and 8.1 mg/kg for fish whole bodies (USEPA, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Redear sunfish were selected as the target species for this study for a variety of reasons, including: 1the relative abundance of this species of fish at each of the proposed study locations, as verified by preliminary sampling; (2) sufficient body and ovary sizes to provide tissues for metal analyses as well the number of eggs needed for crossing trials; (3) relatively high body burdens of Se at the coal-ash exposed study sites (Arcadis, 2012;Otter et al, 2012;Mathews et al, 2014); (4) a known sensitivity of this species to the adverse reproductive effects of Se exposure from coal ash settling basin discharges (Sorensen, 1988); and (5) a relatively compact home-range which contributes to a much greater sitefidelity than larger top-predators in the area such as largemouth bass. [Although the home-range of the redear sunfish is not well-documented, sunfish in general demonstrate a relatively high degree of siteaffinity (Etnier and Starnes, 1994), with the home range of the closely-related pumpkinseed (Lepomis gibbosus) being estimated to be only about 1 hectacre (Warren, 2009).…”
Section: Target Fish Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge of Se-rich fly ash effluent into Martin Lake, TX was followed by liver and ovarian alterations with reduced reproductive success in adult redear sunfish ( Lepomis microlophus ) (Sorensen, 1988). Coal ash spills in Kingston, TN and more recently in the Dan River, NC released 4.1 million m 3 and 39,000 tons of Se-rich coal ash, respectively, threatening birds and fish in those ecosystems (Lemly, 2015; Mathews et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, the concentrations of contaminants were not associated with any lethal or sublethal physiological effects [57,58]. Downstream of the ash spill redear sunfish (Lepomis microlophus), a species likely to have a diet predominantly of aquatic organisms, were found to have elevated levels of Se [59] and evidence of possible sublethal physiological changes [60]. In contrast to the aforementioned studies, Sousa et al [61] found no evidence of metal bioaccumulation or negative health effects in raccoons (Procyon lotor) from the spill site that could be attributed to the ash.…”
Section: Ecological Relevance Of Contaminant Exposuresmentioning
confidence: 99%